If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 44 = x + -12 Reorder the terms: 44 + 2x = x + -12 Reorder the terms: 44 + 2x = -12 + x Solving 44 + 2x = -12 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 44 + 2x + -1x = -12 + x + -1x Combine like terms: 2x + -1x = 1x 44 + 1x = -12 + x + -1x Combine like terms: x + -1x = 0 44 + 1x = -12 + 0 44 + 1x = -12 Add '-44' to each side of the equation. 44 + -44 + 1x = -12 + -44 Combine like terms: 44 + -44 = 0 0 + 1x = -12 + -44 1x = -12 + -44 Combine like terms: -12 + -44 = -56 1x = -56 Divide each side by '1'. x = -56 Simplifying x = -56
| 2(w-6)+2(w)=3(w+8) | | (e+5)*4= | | 0.5(2n+6)=0.2(8n-10) | | Y+-12=11 | | 5.95+0.06m=30 | | 4+11y-1=9y+21-7y | | 8(X-4)=350 | | 42-4X=200 | | 1-x=.4 | | 1.5(x+8)=5.7+0.6x | | 5x+113=11x-7 | | 2x-(5x+2)=9x-26 | | 3y-5=-8(6+5t) | | 11(t-3)+3t=7(2t+4)-10 | | 4x-7=-2x-19 | | 8.99(85)=650+x | | 6+25x=20x+8 | | 8(x-5)-6x=-26 | | 0.5x(y-z)= | | 5.45=14.8-2.2t | | -22=4w+2(w+4) | | y+24=11 | | 7(3x+6)=21x-10 | | (p+7)(-2)= | | -33=5(v-3)-2v | | x=-1/2*4 | | 8.99(x)=1050+335 | | -(3r-2)=-4-4r | | -5y+8=10+y | | x+3-3(5x+15)=5 | | -4+3x=-6+10x | | 12x^2y^4-3x^5+9x^3y^2=0 |